Kemitraan Kelompok Tani Dengan Dinas Pertanian Peternakan Perikanan Pada Kegiatan Sekolah Lapangan Pengelola Tanaman Terpadu (SL-PTT) di Kota Tomohon - Motulo, Yuvita Santi; Tampi, J. Revo E.; Londa, Very Y. (JURNAL ILMIAH SOCIETY, 2015)
Partnership activities are broadly aims to increase revenue, business continuity, improve quality resource partner groups, the increase in the scale of business, in order to foster and enhance the ability of independent partners group looks not as expected. This study aims to reveal and analyze partnerships undertaken by the farmer groups with the Department of Agriculture, Livestock Fisheries on business activities of Integrated Crop Field School (FFS-ICM) in Tomohon.The data in this study were obtained through interviews with informants farmer groups and employees of the Department of Agriculture Livestock Fisheries betangungjawab on partnership activities. The results of this study indicate that partnerships undertaken by the farmer groups with the Department of Agriculture, Livestock Fisheries on business activities of Integrated Crop Field School (FFS-ICM) in Tomohon in the form of co-operation to improve poduktivitastanaman rice and maize have not done well as the principles of trust, respect and expectations.Keywords: Partnerships, Farmers Group, Integrated Crop Management.